AN ORDER OF FORMING AND DRAWING ON RESERVED IS UNDER CREDIT RISKS IN BANK OF UKRAINE - Нездойминога, О. Є. (Scientific Progress & Innovations, 2014)
Вasic tendencies are investigational in realization of activeoperations bank institutions. Essence of credit risk, external and internal factors of influence is certain on him. Classification of credit to the brief-case bank is considered and the categories of credit operations after the level of credit risk and corresponding norms of withholdings are to reserve under the credit risks of banks of Ukraine. The order of forming and drawing on reserves is reflected under the credit risks of banks of Ukraine.